Comparative Study of Al2O3 and HfO2 for Surface Passivation of Cu(In, Ga)Se2 Thin Films: An Innovative Al2O3/HfO2 Multistack Design. Issue 14 (6th June 2021) - Scaffidi, Romain; Buldu, Dilara G.; Brammertz, Guy; de Wild, Jessica; Kohl, Thierry; Birant, Gizem; Meuris, Marc; Poortmans, Jef; Flandre, Denis; Vermang, Bart
Abstract : In Cu(In, Ga)Se2 (CIGS) thin‐film solar cells, interface recombination is one of the most important limiting factors with respect to device performance. Herein, metal–insulator–semiconductor samples are used to investigate and compare the passivation effects of Al2 O3 and HfO2 at the interface with CIGS. Capacitance–voltage–frequency measurements allow to qualitatively and quantitatively assess the existence of high negative charge density ( Q f  ≈ −10 12  cm −2 ) and low interface‐trap density ( D it  ≈ 10 11  cm −2  eV −1 ). At the rear interface of CIGS solar cells, these, respectively, induce field‐effect and chemical passivation. A trade‐off is highlighted between stronger field‐effect for HfO2 and lower interface‐trap density for Al2 O3 . This motivates the usage of Al2 O3 to induce chemical passivation at the front interface of CIGS solar cells but raises the issue of its processing compatibility with the buffer layer. Therefore, an innovative Al2 O3 /HfO2 multistack design is proposed and investigated for the first time. Effective chemical passivation is similarly demonstrated for this novel design, suggesting potential decrease in recombination rate at the front interface in CIGS solar cells and increased efficiency. 300 °C annealing in N2 environment enable to enhance passivation effectiveness by reducing D it while surface cleaning may reveal useful for alternative CIGS processing methods. Abstract : The versatility of Al2 O3 and HfO2 as potential passivation layers for CIGS solar cells is demonstrated. Either Al2 O3 or HfO2 can be used to passivate the rear interface, with a tradeoff between stronger field‐effect for HfO2 and lower interface‐trap density for Al2 O3 . Chemical passivation of the front interface is suggested possible with an innovative Al2 O3 /HfO2 multistack design.